Trends in Gender Equality and Women's Advancement - Stotsky, Janet; Kebhaj, Suhaib; Kolovich, Lisa.; Shibuya, Sakina (Washington, D.C. : International Monetary Fund, 2016)
This paper examines trends in indicators of gender equality and women's development, using evidence derived from individual indicators and gender equality indices. We extend both the United Nations Development Program's Gender Development Index and Gender Inequality Index to examine time trends. In recent decades, the world has moved closer to gender equality and narrowed gaps in education, health, and economic and political opportunity; however, substantial differences remain, especially in South Asia, the Middle East, and sub-Saharan Africa. The results suggest countries can make meaningful improvements in gender equality, even while significant income differences between countries remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet